2020
DOI: 10.3390/plants9040513
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Expression Analysis and Functional Study of CCT Gene Family in Medicago truncatula

Abstract: The control of flowering time has an important impact on biomass and the environmental adaption of legumes. The CCT (CO, COL and TOC1) gene family was elucidated to participate in the molecular regulation of flowering in plants. We identified 36 CCT genes in the M. truncatula genome and they were classified into three distinct subfamilies, PRR (7), COL (11) and CMF (18). Synteny and phylogenetic analyses revealed that CCT genes occurred before the differentiation of monocot and dicot, and CCT orthologous genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…It was reported that over-expression of TOC1, a key component of the circadian clocks belonging to CCT family, significantly reduced the drought tolerance in Arabidopsis [24]. Moreover, the biorhythm-related CCT family genes in Medicago truncatula responded to NaCl stress [25]. In plants, WD40 proteins were involved in plant development, response to stress and other physiological activities [26,27].…”
Section: Hpxbcp3 Responded To Nacl Stress In Microalgaementioning
confidence: 99%
“…It was reported that over-expression of TOC1, a key component of the circadian clocks belonging to CCT family, significantly reduced the drought tolerance in Arabidopsis [24]. Moreover, the biorhythm-related CCT family genes in Medicago truncatula responded to NaCl stress [25]. In plants, WD40 proteins were involved in plant development, response to stress and other physiological activities [26,27].…”
Section: Hpxbcp3 Responded To Nacl Stress In Microalgaementioning
confidence: 99%
“…Recently, Ma et al [ 86 ] reported a comprehensive analysis of 36 circadian-related genes, namely those containing the CCT domain. The CCT ( CONSTANTS-CONSTANS LIKE-TIMING OF CAB 1 ) genes have been previously implicated in flowering time regulation and biomass accumulation [ 87 ].…”
Section: Legume Clock Research At a Glancementioning
confidence: 99%
“…The CCT ( CONSTANTS-CONSTANS LIKE-TIMING OF CAB 1 ) genes have been previously implicated in flowering time regulation and biomass accumulation [ 87 ]. Gene clustering analysis for barrel medic associated the CCT genes with flowering time regulation, abiotic stress response, and regulation of growth and development [ 86 ]. A recent study revealed that the LHY ( LATE ELONGATED HYPOCOTYLS ) gene also plays an essential role in the regulation of the endogenous biological clock in barrel medic [ 48 ].…”
Section: Legume Clock Research At a Glancementioning
confidence: 99%
“…Our previous investigation suggested that natural populations of O. rufipogon exhibited clinal variation in flowering time from north to south within its range in China ( Gao et al, 2000 ). The CCT TFs have been identified and functionally elucidated in several crop species, such as rice ( Zhang et al, 2017 ), maize ( Huang et al, 2018 ), wheat ( Yan et al, 2004 ), barley ( Turner et al, 2005 ), and Medicago truncatula ( Ma et al, 2020 ). However, functional roles of CCT TFs have not been elucidated in their wild progenitors, such as O. rufipogon in this study.…”
Section: Introductionmentioning
confidence: 99%